2014
DOI: 10.1364/ao.53.006351
|View full text |Cite
|
Sign up to set email alerts
|

Flame spectra-temperature estimation based on a color imaging camera and a spectral reconstruction technique

Abstract: In this paper a low-cost, practical pixel-based flame spectrum and temperature estimation system based on flame color images is proposed. A spectral resolution of ∼ 0.4 nm is achieved with an optical system formed by a color camera, a linear model, a flame's spectral training data, and a spectral reconstruction procedure. As a proof of concept, the estimated spectra are compared to local measurements performed with a commercial spectrometer. In order to estimate the absolute flame-temperature maps, two radiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…As reported in the literature [2,[4][5][6], spectroscopy and optical techniques are suitable, nondestructive and contactless sensing alternatives to characterize combustion processes. In particular, some authors have reported the FeO spectral emission pattern in the visible (VIS) spectral range as reported by West and Broida in their work [7].…”
Section: Introductionmentioning
confidence: 99%
“…As reported in the literature [2,[4][5][6], spectroscopy and optical techniques are suitable, nondestructive and contactless sensing alternatives to characterize combustion processes. In particular, some authors have reported the FeO spectral emission pattern in the visible (VIS) spectral range as reported by West and Broida in their work [7].…”
Section: Introductionmentioning
confidence: 99%
“…Linear basis vectors were calculated by using principal components analysis (PCA). PCA was chosen because it has been previously verified to provide the most accurate spectral matching results, using a few of both the optical channels and principal components, compared to the non-negative matrix factorization (NNMF) and independent component analysis (ICA) reduction methods [46,51]. Thus, PCA was computed over the training spectral data L. Figure 3a depicts the first to fourth principal components, as a function of wavelength λ, where the fourth component and the subsequent basis vectors only contain negligible information.…”
Section: Methodsmentioning
confidence: 99%
“…where ρ is a k-by-one vector containing the optical sensor pixel response, E is an N-by-one column vector representing the incident spectrum, and Ω is an N-by-k matrix containing the spectral sensitivity vectors of the optical channels (T is the transpose function). In practice, spectral sensitivity vectors in Ω features any optical sensor in a mathematical way and represents the transmittance of the filters of the optical sensor weighted by its quantum efficiency [46,47]. We will consider that the additive noise e could be neglected and the spectral sensitivity vectors in Ω are known.…”
Section: Spectral Retrievalmentioning
confidence: 99%
See 2 more Smart Citations